2014
DOI: 10.1590/1806-9282.60.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low bone mineral density in adolescents and adults with cystic fibrosis

Abstract: Prevalence of low bone mineral density in adolescents and adults with cystic fibrosis rev assoc med bras 2014; 60 (1) Conflict of interest: noneObjective: The aim of this cross-sectional study was to evaluate the prevalence of low bone mass density in cystic fibrosis patients as well as to evaluate the factors associated with bone mass in such patients. Methods: Bone mass density was measured by dual-photon X-ray absorptiometry of lumbar spine (L1-L4), in patients ≤19 years old, or lumbar spine and femur (tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
2
1
1
Order By: Relevance
“…The prevalence of bone mineral density (BMD) z-scores below − 1 SD was 10% in our study, but it has been reported to be as high as 85% in some adult CF studies [9]. On the other hand, there are some cross-sectional surveys showing that pre-pubertal children with CF do not have a bone mineral deficit compared with a weight-and sex-matched control groups [35][36][37][38]. The reasons for the discrepancy in the findings include: differences in measurement and analytic techniques that adjust for impaired growth and maturation in CF patients, disease severity, reference data, and the lack of consensus in defining impaired bone health in children.…”
Section: Discussioncontrasting
confidence: 62%
“…The prevalence of bone mineral density (BMD) z-scores below − 1 SD was 10% in our study, but it has been reported to be as high as 85% in some adult CF studies [9]. On the other hand, there are some cross-sectional surveys showing that pre-pubertal children with CF do not have a bone mineral deficit compared with a weight-and sex-matched control groups [35][36][37][38]. The reasons for the discrepancy in the findings include: differences in measurement and analytic techniques that adjust for impaired growth and maturation in CF patients, disease severity, reference data, and the lack of consensus in defining impaired bone health in children.…”
Section: Discussioncontrasting
confidence: 62%
“…Furthermore, stratification of the patients according to faecal elastase‐1 levels resulted in significant variations of vitamin D3 between the subgroups . In cystic fibrosis, a condition regularly associated with pancreatic exocrine insufficiency, a decrease in BMD has been noted in several studies . Furthermore, no improvement in skeletal health was observed in these patients compared to patients from the late 1990s .…”
Section: Systematic Literature Review Of Age‐related Pancreatic Functmentioning
confidence: 99%
“…[16] The association between low BMD and airway clearance impairment and/or decline of respiratory function has not been demonstrated. [11,13,17,18] Some authors consider that osteoporosis may be a barrier to lung transplantation. [19,20] Interestingly, we found no association between spinal pain and low BMD in our study.…”
Section: Discussionmentioning
confidence: 99%